Laparoscopic peritoneal lavage: our experience and review of the literature - Amilcare Parisi; Alessandro Gemini; Jacopo Desiderio; Adolfo Petrina; Stefano Trastulli; Veronica Grassi; Marco Sani; Daniele Pironi; Alberto Santoro (Videosurgery and Other Miniinvasive Techniques)
Introduction : Over the years various therapeutic techniques for diverticulitis have been developed. Laparoscopic peritoneal lavage (LPL) appears to be a safe and useful treatment, and it could be an effective alternative to colonic resection in emergency surgery. Aim : This prospective observational study aims to assess the safety and benefits of laparoscopic peritoneal lavage in perforated sigmoid diverticulitis. Material and methods : We surgically treated 70 patients urgently for complicated sigmoid diverticulitis. Thirty-two (45.7%) patients underwent resection of the sigmoid colon and creation of a colostomy (Hartmann technique); 21 (30%) patients underwent peritoneal laparoscopic lavage; 4 (5.7%) patients underwent colostomy by the Mikulicz technique; and the remaining 13 (18.6%) patients underwent resection of the sigmoid colon and creation of a colorectal anastomosis with a protective ileostomy. Results : The 66 patients examined were divided into 3 groups: 32 patients were treated with urgent surgery according to the Hartmann procedure; 13 patients were treated with resection and colorectal anastomosis; 21 patients were treated urgently with laparoscopic peritoneal lavage. We had no intraoperative complications. The overall mortality was 4.3% (3 patients). In the LPL group the morbidity rate was 33.3%. Conclusions : Currently it cannot be said that LPL is better in terms of mortality and morbidity than colonic resection. These data may, however, be proven wrong by greater attention in the selection of patients to undergo laparoscopic peritoneal lavage.